Analisis Perbedaan Tingkat Profitabilitas Sebelum Dan Selama Pandemi Studi Pada Sektor Tekstil Di Bursa Efek Indonesia - Celine Esthelica; Frizar Abdul Azis Budiman; Jasmine Aliyah; Siti Amelia (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to analyze differences in the level of company profitability before and during the COVID-19 pandemic. The data used in this study were taken from financial reports listed on the official IDX website. The samples in this study were 8 textile companies that reported their financial statements on the IDX in 2019 and 2020. The data analysis method used in this study was the Wilcoxon test and the different test method or paired sample t-test. This study uses the method of financial ratio analysis to calculate the company's profitability ratios. The analysis was performed by calculating the proximate profitability ratios using Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin (GPM), and Net Profit Margin (NPM). The results of the study show that the average company profitability ratio decreased, but not significantly during the COVID-19 pandemic when compared to the pre-pandemic period in textile manufacturing companies.